The Effect of Cyclo-oxygenase Inhibition on Systemic Cytokine-Acute Phase Protein Response After Gastrointestinal Surgery (Annals of Medical Research, 2021)
None
Keywords: s : Cytokine, acute phase proteins, piroxicam